IMPLEMENTASI PROGRAM BANTUAN PANGAN NON TUNAI DI KECAMATAN LONG BAGUN KABUPATEN MAHAKAM ULU - Martina Lunau (Jurnal Paradigma (JP), 2022)
Abstract: The purpose of the study was to analyze the implementation Bantuan Pangan Non Tunai (BPNT)  Sembako in Long Bagun District, Mahakam Ulu Regency, and examine the supporting and inhibiting factors for its implementation. The research approach is descriptive qualitative with analytical techniques using interactive model analysis. The results of this study indicate that the implementation of Bantuan Pangan Non Tunai (BPNT)  in Long Bagun District has been running according to the mechanism in the general guidelines, starting from the preparation stage carried out in coordination with the Central Government, the ranks of stakeholders in the region to the village level. The implementation has also been carried out correctly by the general guidelines. The Education/Socialization phase has been carried out starting from the registration and distribution phase. Then in the distribution stage, it is carried out by Bank BRI. Furthermore, the location of utilization and distribution of assistance has been according to a predetermined schedule. However, the inhibiting factors found were the low capacity of the sub-district apparatus and villages and the difficulty of accessing the sub-districts and village in the interior at the time of distributing and socializing. Then another inhibiting factor was the limited internet network in Mahakam Ulu Regency. Keywords: Non-Cash Food, Implementation, Long Bagun, Mahulu.